Error Analysis of Students’ Comment Writing in Online Learning at FLSP Class - Fawaid, Anas; Raunaq, M Nabriis; Mustofa, Mutmainnah (IJET (Indonesian Journal of English Teaching), 2022)
Grammatical errors are one of the issues that students face during the writing process. The main goal of this research was to discover the most common grammatical errors committed by FLSP students in comment writing at the University of Muhammadiyah Malang in 2021. The goal of this study was to distinguish, categorize, and display the percentage of students that committed each sort of error. The research approach employed was qualitative and descriptive methods. This study included 30 first semester students as participants in the Communication (A), Accounting (B), Elementary School Teachers (D), Psychology (J), Engineering at FLSP class of UMM. Documentation of student comment writing debate was utilized as the tool. The Surface Strategy Taxonomy, developed by Dulay et al., is used to assess all grammatical mistakes found in student comments in Canvas (LMS). According to the findings, there are a total of 230 errors. The most common error was omission (120 errors / 52.18 percent), followed by misformation (70 errors / 30.43 percent), addition (30 errors / 13.14 percent), and misordering (10 errors / 4.38 percent). Based on these findings, it can be inferred that students continue to struggle with understanding grammatical structures throughout the writing process.